Alcohol is a great destroyer: A call for insight on ceremonial approaches for coping with FASD - Koptie, Steven (First Peoples Child & Family Review, 2013)
As a seasoned community helper, I worry about the generation now assuming roles as healers, leaders and warriors, and continuing the fight for fundamental change in the relationship between Canada’s Indigenous peoples and those privileged to inherit colonial legacies of European global colonization. I now view my personal journey of self discovery as an unending marathon. I honour “Runners” like Tom Longboat who represented the strength and vitality of healthy and sober communities. Traditional runners were as dependent on path-finders as we are today, yet they travelled with dedication and carried important information that sustained community integrity. Open discussion about the devastation of FASD is the most important conversation required across our territories today. We need to prepare good messages and good minds for the next generation to bring forward. This self-reflective paper seeks solace in rituals such as the Haudenasaunee Reqickening Addresses to allow those who suffer to “stand again in front of the people.”